2021
DOI: 10.1016/j.rmed.2021.106530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surgical and cloth facemasks during a submaximal exercise test in healthy adults

Abstract: Background Surgical (SM) or cloth facemasks (CM) has become mandatory in many public spaces during the COVID-19 pandemic. They may interfere with the participation in physical activities. Objective To evaluate how these masks influence dyspnoea (primary outcome), exercise performance and cardiorespiratory response during a 1-min sit-to-stand test (1STST), and to assess masks discomfort sensations. Methods A randomized crossover trial was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 40 publications
5
39
1
1
Order By: Relevance
“…These findings are in agreement with the results of Li et al who previously observed that the discomfort associated with the use of a surgical facemask was not impacted during rest periods [22]. Moreover, findings from a recent study with a similar design but conducted in adults highlighted that the surgical facemask had no immediate effect on HR, SpO2, or dyspnea [23]. To our knowledge, this is the first study performed in children that evaluated the effect of a facemask during a 1-min submaximal exercise test that reflects the physical level of daily life activities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in agreement with the results of Li et al who previously observed that the discomfort associated with the use of a surgical facemask was not impacted during rest periods [22]. Moreover, findings from a recent study with a similar design but conducted in adults highlighted that the surgical facemask had no immediate effect on HR, SpO2, or dyspnea [23]. To our knowledge, this is the first study performed in children that evaluated the effect of a facemask during a 1-min submaximal exercise test that reflects the physical level of daily life activities.…”
Section: Discussionsupporting
confidence: 92%
“…The STST does not reflect sporting activities where the duration and the intensity of the effort are different. Our results have also to be extrapolated with caution to other facemasks as the cloth facemask [23]. The powers of filtration or absolute humidity inside these facemask [22], and then the related resistances can differ.…”
Section: Discussionmentioning
confidence: 80%
“…The World Health Organization (WHO) advises that wearing a mask during vigorous physical activities increases breathing difficulties [ 15 ], with reduced oxygen uptake and increased carbon dioxide rebreathing [ 15 ]. Reychler G et al [ 16 ] found that healthy adults wearing a surgical mask had no influence on dyspnea, respiratory rate, heart rate, oxygen saturation and exercise performance during a short submaximal exercise test. Healthy volunteers wearing surgical masks experienced higher dyspnea than those without masks, but this did not impact results after a 6MWT [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 19 , 20 A recent study found that the intensity of the 1-min sit-to-stand test was not sufficiently high to elicit an increase in dyspnoea sensation with the surgical mask in young healthy adults. 21 A clinically relevant increase in dyspnoea was only noted at the end of the sit-to-stand test with the cloth mask, probably because this mask opposed more resistance to airflow than the surgical mask. 21 In contrast, this study found that acute COVID-19 patients near hospital discharge experienced a significant and clinically relevant dyspnoea sensation at rest, as soon as the surgical mask was worn.…”
Section: Discussionmentioning
confidence: 97%
“… 21 A clinically relevant increase in dyspnoea was only noted at the end of the sit-to-stand test with the cloth mask, probably because this mask opposed more resistance to airflow than the surgical mask. 21 In contrast, this study found that acute COVID-19 patients near hospital discharge experienced a significant and clinically relevant dyspnoea sensation at rest, as soon as the surgical mask was worn. Although our patients were recovering from COVID-19, they still presented impaired cardiorespiratory fitness as shown by the abnormally elevated respiratory rate and low oxygen saturation values at ambient air before the sit-to-stand test ( Table 3 ).…”
Section: Discussionmentioning
confidence: 97%